Finitude, Aging and Subjectivity - Correa, Mariele Rodrigues; Hashimoto, Francisco (Revista Kairós-Gerontologia, 2014)
The purpose of this article is to analyze the relationship of man with death and its deployment in subjectivity and in aging. With this intent, we first present a brief history of the vision of death over time and after an analysis of the process of aging and dying according to the logic of biopolitical management. With death and old age increasingly distant from the horizons of life, subjectivity has been weakened. Thus, incorporating these aspects as part of existence constitutes one of the challenges to the thought as well as to the building of the self.